Current and future approaches to nonclinical cardiovascular safety assessment. Issue 7 (July 2020) - Collins, Teresa A.; Rolf, Michael G.; Pointon, Amy
Highlights: Developing newer modalities requires bespoke cardiovascular safety assessment. Monitorable approaches to structural cardiotoxicity ensured clinical progression. Link from in vitro inhibition to clinical response guided chemical design. Disease models offer assessment of patient-relevant therapeutic index. Focus developments in humanised models, mechanism and patient predictions. Abstract : Our goal is to accurately predict all types of cardiovascular events in patients utilising nonclinical cardiovascular safety data. In the past two decades, cardiovascular safety science has primarily focused on events associated with the electrocardiogram. Broadening out to other cardiovascular parameters, we share real-life case studies that highlight our progress towards improved and better-informed project progression based upon use of disease models, mechanism-based translation and structure–function relationships. To fulfil this goal, further advances in patient-relevant humanised models will be required to enable cardiovascular safety science to keep pace with the ever-changing landscape of novel therapeutic paradigms.